Effects of intracanal cryotherapy on postoperative pain in necrotic teeth with symptomatic apical periodontitis: a randomized controlled clinical trial - Ahmad, Muhammad Zubair (Frontiers in Dental Medicine, 2025)
ObjectivesThe present study aimed to assess the effects of intracanal cryotherapy on pain following single-visit non-surgical root canal treatment (NSRCT) of molar teeth with pulpal necrosis and symptomatic apical periodontitis (SAP).MethodsThis parallel-two arm, single-blind, randomized superiority clinical trial was registered at www.clincaltrials.gov (NCT05611736). Patients referred for NSRCT meeting the inclusion criteria were included. Preoperative radiographs, pulp sensibility tests, and pain scores on the visual analog scale (VAS) were recorded. Following shaping and cleaning, 302 patients were randomly allocated to the two groups (n = 151). In the experimental group, final irrigation was done using 0.9% physiologic saline solution at 2.5 °C, whereas in the control group, final irrigation was done using the same solution at room temperature. All treatments were performed in a single visit. Analgesics intake and presence, duration, and intensity of pain using the VAS at 6, 24, 72 h, and 1 week were recorded. Any adverse events were recorded. Data was analyzed using the Mann–Whitney U test and the Student's t test (P < 5%).ResultsPatients in the cryotherapy group had significantly less postoperative pain at 6, 24, and 72 h (P < 0.05). There was no difference in postoperative pain at 1 week (P > 0.05). No adverse event was recorded in either group during or immediately after root canal treatment.ConclusionCryotherapy significantly reduces postoperative pain in single-visit root canal treatment of molars with pulp necrosis and SAP. It can be considered a biocompatible, economical, and straightforward method for managing postoperative pain.Clinical Trial Registrationwww.clincaltrials.gov, identifier (NCT05611736).